Legal and Economic Reglamentation Aspects of Individual Enterprise Functioning - Perkumienė, Dalia; Čiulevičienė, Vida (Ekonomika, 2008)
The operation of individual enterprises established in Lithuania was regulated by various separate laws which caused much inconvenience. Therefore, the Lithuanian law on individual enterprises entered into force on 1 January 2004. The article aims to present the outstanding peculiarities of an individual enterprise as a legal entity which could be considered as advantages and disadvantages. The article considers the individual enterprise before and after the entry into force of the Lithuanian law on individual enterprises.